PERANCANGAN APLIKASI PENJUALAN DENGAN METODE WATERFALL PADA KOPERASI KARYAWAN RSUD PASAR REBO - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
Computer is a piece of equipment that was created to facilitate the work of the human, while achieving progress in making hardware or software. RSUD Pasar Rebo Employees Cooperative need once the presence of a system of information support and provide satisfying service for our customers. For that is the writer trying to make a research regarding the system of sale of goods in RSUD Pasar Rebo Employees Cooperative has not been well-managed. So often times error record keeping, less accurately the report made and the delay in the search for the required data. The Application of this information system is the best solution to solve the problems existing in the company, as well as with the computerized system that can be reached by an activity which is effective and efficient in support of activities in the company. The computerized system is better than the manual systems to run more effectively and efficiently, as well as the sales system is now more conducive than with previous systems.